Mahatma Gandhi’s Concept of Educational Leadership - Joseph, Philip (International Journal of Economics, Business and Management Studies, 2012)
The author endeavors to track the origin and evolution of Mahatma Gandhi’s philosophy of education with focus on management and leadership style through his successive experimental schools in South Africa and India. He further explores the transformational thrust of Gandhi’s leadership. He argues Gandhi was a unique and charismatic leader who inspired his followers to commit themselves into real action, empowering them as leaders and making them agents of normative social change. Gandhi’s transformational leadership brought about unprecedented positive differences among the members of his ashram schools. He took them to levels of thinking, feeling and action they never thought they could ever attain.